PENYAKIT LAYU Ralstonia solanacearum PADA KACANG TANAH DAN STRATEGI PENGENDALIAN RAMAH LINGKUNGAN - Mudji Rahayu (Buletin Palawija, 2012)
Bacterial wilt caused by Ralstonia solanacearumis an important disease constraint of groundnut(Arachis hypogaea L.) in tropical and subtropical allover the world. It causing yield losses of 15–35%,and may reach over 65% in groundnut susceptiblevarieties. In Indonesia, the disease have been foundin some areas in North and West Sumatra, Lampung,West Java, Central Java, East Java, Bali, North andSouth Sulawesi. The wilt symptoms can be observedthree weeks after sowing. Infection of plants resultsin rapid wilting of stems and foliage, while leavesretain their green color.There is no desirable method for chemical controlof groundnut wilt, although some bactericidesthat effective against R. solanacearum have beenidentified and available commercially. Other controlstrategy by non-chemically include resistant varieties,healthy seeds, healthy cultivation, biologicalcontrol, and botanical control have been reduced thedisease. Other disease control strategies which ereenvironment-friendly are resistant variety, and theuse of bio control agents. Resistance variety is oneof the most effective means of controlling groundnutwilt and effective to control bacterial wilt in endemicarea and this method could be adopted byfarmer easily. Biocontrol agents i.e. antagonisticbacteria Psudomonas fluorescens (Pf) isolated fromlegumes rhizosphere showed inhibited effect againstbacterial wilt R. solanacearum. The plants extractof some plants such as lemon grass and nut sedgeroots, also showed suppressive effect against bacterialwilt of groundnut.